Diagnosis Penyakit Diabetes pada Masyarakat Awam Menggunakan Metode Backward Chaining - Don Luthvan (Rektorat Universitas Putra Indonesia YPTK Padang, 2019)
Expert system is a system that seeks to adopt human knowledge into computers, this research was conducted to diagnose diabetes early. Disease data that were processed were sourced from the South Solok District General Hospital. The method used is Backward Chaining by using a goal-driven approach. The result of testing this method is that the user understands the danger of diabetes and knows how to prevent it. Trials conducted on an expert system for diagnosing diabetes, most people understand the characteristics and symptoms of diabetes and understand how to prevent it. So that this expert system can be recommended for ordinary people.